Demographic characteristics and clinical manifestations of interstitial lung disease with systemic sclerosis in eastern part of Libya - Fathi Elbraky; Khaled Alsaeiti; Fathiyah Aboulqasim; Saleh Alawgali (Libyan International Medical University Journal)
Introduction: Pulmonary involvement, such as Interstitial Lung Disease (ILD) and Pulmonary Hypertension (PH ), accounts for significant morbidity and is the leading cause of Systemic sclerosis (SSc)-related morbidity and mortality. The aim of the current study was to study the frequency of occurrence of ILD in SSc and to describe the clinical and radiological picture of pulmonary involvement in SSc. Patients and Methods: Forty patients attending different rheumatology clinics in eastern part of Libya between January 2018 and September 2020 were included. Basic details including age, gender, disease duration, detailed history, and clinical examination were noted. Autoimmune profiling included rheumatoid factor, antinuclear antibodies, and anti-Scl-70 antibodies. Pulmonary function test, chest X-ray (CXR), and high-resolution computed tomography of the chest (HRCT) in all patients were recorded. Data presented either as frequencies and percentages or as means ± standard deviation. Results: The male: female ratio was 1:9 with a mean age of 37.5 ± 9.6 years and duration of illness 6 ± 4 years. diffuse cutaneous SSc was seen in 62.5% of the patients. 77.5% of the participants had bilateral crepitation and 57.5% had loud P2. Presenting complaints included gastrointestinal reflux in 72.5%, digitalis ulcerations in 40%, and synovitis/arthritis of all patients. Other comorbidities included congestive heart failure in 12.5%, PH in 15%, and renal impairments in 7.5% of all patients. Anti-Scl-70 antibody was the most common in all patients (45%), followed by anti-centromere Ab (25%), anti-U3 RNP (10%), and anti-U1 RNP (5%). 72.5% of the participants had reticulonodular shadows on CXR. HRCT showed honeycombing as the predominant finding (37.5%). Echocardiograms showed that 15% of all patients have signs of PH. Duration of disease, dyspnea, cough, bilateral crepitations, and CXR were found to be significantly associated with extensive ILD (P < 0.05). Conclusion: ILD is a serious complication of SSc, it is more common among patients with dcSSc. Chest HRCT is very sensitive to detect ILD. A significant association was found in Libyan patients between the severity of ILD and the duration of disease, dyspnea, cough, bilateral crepts, and CXR.